2023
DOI: 10.3389/fnins.2023.1135689
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of iTBS on the muscle activation pattern under challenging balance conditions in the patients with chronic low back pain: A preliminary study

Abstract: BackgroundThe patients with chronic low back pain (CLBP) showed impaired postural control, especially in challenging postural task. The dorsolateral prefrontal cortex (DLPFC) is reported to involve in the complex balance task, which required considerable attentional control. The effect of intermittent theta burst stimulation (iTBS) over the DLPFC to the capacity of postural control of CLBP patients is still unknown.MethodsParticipants diagnosed with CLBP received a single-session iTBS over the left DLPFC. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This is the first study that has trialled iTBS in this population and was chosen as the pre-treatment due to its potential to enhance synaptic plasticity, promote synaptogenesis, and facilitate synaptic connections within cortical tissue [ 82 85 ], with the aim to enhance the brain’s responsiveness for subsequent treatments. Further, iTBS over DLPFC has previously been shown to enhance postural control among other population groups [ 86 ]. iTBS also requires less session time compared to rTMS protocols [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study that has trialled iTBS in this population and was chosen as the pre-treatment due to its potential to enhance synaptic plasticity, promote synaptogenesis, and facilitate synaptic connections within cortical tissue [ 82 85 ], with the aim to enhance the brain’s responsiveness for subsequent treatments. Further, iTBS over DLPFC has previously been shown to enhance postural control among other population groups [ 86 ]. iTBS also requires less session time compared to rTMS protocols [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current study utilised an excitatory iTBS protocol, based on the positive effects observed in people with MdDS after excitatory rTMS over left DLPFC [ 33 , 34 ]. iTBS over DLPFC has been shown to improve postural control in other population groups [ 86 ], though has not been trialled in people with MdDS. The goal of the protocol used in this study was to decrease functional connectivity between the entorhinal cortex and the posterior default mode network, in accordance with the findings of Yuan and colleagues [ 41 ], where positive outcomes were associated with a decrease in functional connectivity after excitatory rTMS over the left DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…The DLPFC, specifically in the right hemisphere, has been suggested to play a role in pain, emotion, and social decision-making 24 . Recent literature has suggested that iTBS over the left DLPFC can improve muscle activation patterns during challenging postural control tasks, providing a new approach to treating chronic low back pain 25 . We further confirmed the role of this treatment method in pain treatment.…”
Section: Discussionmentioning
confidence: 99%